Supernatural, Humanity, and the Soul - George, Susan A. author. aut Link
XII, 223 p. 15 illus.
Keywords: Through nine seasons the TV show Supernatural has delved into social, philosophical, literary, and theological themes that not only add depth to the show, but reflect our era's intellectual concerns. This book contextualizes Supernatural within the renaissance of the fantastic in pop culture and traces its roots in folklore and Biblical narrative.